(+)‐Sparteine‐Mediated Substitution of o‐Benzyl‐N‐pivaloylaniline with Ketones. Issue 16 (10th April 2014) - Ko, Yi Kyung; Im, Chan; Do, Junghwan; Park, Yong Sun
Abstract: The (+)‐sparteine‐mediated lithiation–substitution of o ‐benzyl‐ N ‐pivaloylaniline with various ketones was investigated. The obtained highly enantioenriched tertiary alcohols were used for the synthesis of alkenyl‐substituted products12 and13 as well as 3, 3, 4‐trisubstituted tetrahydroquinoline derivatives22 –24 . The reaction with α, β‐unsaturated ketones afforded highly enantioenriched 1, 4‐addition products28 –33 and provided a protocol for the asymmetric synthesis of highly substituted tetralin derivative34 . Abstract : The (+)‐sparteine‐mediated lithiation–substitution of o ‐benzyl‐ N ‐pivaloylaniline with various ketones afforded the corresponding tertiary alcohols and 1, 4‐adducts with high enantioselectivity. Moreover, this synthetic method was successfully applied to the syntheses of highly enantioenriched tetrahydroquinolines and tetralin derivatives.